A scientometrics analysis and visualization of refractory gastroesophageal reflux disease - Zhang, Nan; Han, Ming; Zheng, Qin-Wei; Zhang, Meng-Yuan; Zhi, Wen-Lan; Li, Jing-Jing; Cui, Lin-Xuan; Tian, Jin-Li; Wang, Yi; Fang, Sheng-Quan (Frontiers in Pharmacology, 2024)
Refractory gastroesophageal reflux disease (refractory GERD) is a heterogeneous disease characterized by unresponsiveness or poor efficacy to proton-pump inhibitors (PPIs). This chronic disorder substantially weakens patients' mental well-being and quality of life, increasing the financial burden on society. Multiple articles have been reported in this area. However, literature involving scientometric analysis of refractory GERD is absent. Therefore, it is necessary to understand the evolution of research themes and the main hotspots of refractory GERD through bibliometric methods.All documents related to refractory GERD based on the WOS Core Collection from January 2000 to November 2023 were selected for analysis. Citespace V 6.1 R6, VOSviewer V 1.6.20, and Scimago Graphica V 1.0.38 were used to perform bibliometric analysis.We collected a total of 241 research articles from 36 countries and 322 institutions, contributed by over 1000 authors. Over the last 20 years, the number of articles in this field has increased year by year, and since 2011, the number of publications has increased dramatically, with 85.89% of the papers. These countries are led by the United States and Japan. GUT had the highest number of citations and DIGESTION had the highest number of publications.Research on standardized diagnosis and management, mechanisms, novel monitoring methods, and innovative drugs and procedures for refractory GERD are the main topics and hotspots in this field. This study also found that neuroimmune interaction is closely related to refractory GERD, which may be a new direction for future mechanism research.Our study is the first bibliometric analysis of the global literature on refractory GERD. This research provides valuable insights for researchers, enabling them to quickly understand the research frontier and hot topics of this field.